Kaji eksperimen pengaruh hardening dan tempering terhadap kekuatan tarik dan kekerasan pada baja karbon sedang - Akmal Barry; Zuraida Zuraida (Universitas Muhammadiyah Metro, 2022)
This study aims to determine the effect of hardening and tempering on tensile strength (ASTM E 8) and hardness (Rockwell) applied to medium carbon steel. The heat treatment process hardening is heated by a furnace at a temperature of 900 °C and 920 °C then held for 30 minutes and cooled quickly and then further processed by Tempering with each being tempered at 500 °C and cooled slowly. The results obtained are in the hardening process with a temperature variation of 900 °C, the hardness value increases from the raw material value of 5.7 HRC to 7.52 HRC and has increased again at a temperature of 920 °C of 8.08 HRC. Tempering process temperature variation of 900/ 500 °C the value is above raw material by 5.7 HRC to 7.24 HRC, down at a temperature of 920/500 °C by 6.4 HRC. For tensile testing of the hardening process against utimate stress, the value for raw material is 516,095 MPa, temperature is 900 °C/451,065 MPa and temperature is 920 °C/389,625 MPa. for yield strength raw material value is 477.4165 MPa, temperature is 900°C/270.8395 MPa, temperature is 920°C/256.4555 MPa, for modulus raw material value is 347.53 GPa, temperature is 900°C/3452605 MPa , the temperature is 920 °C/338.206 MPa, for the elongation value the raw material value is 7.871%, the temperature is 900 °C/11.392%, the temperature is 920 °C/16.448 %. for tempering to utimate stress the raw material value is 516,095 MPa, temperature 900/500 °C is 417,5635 MPa and temperature 920/500 °C is 372.416 MPa. For yield strength raw material value is 477.4165 MPa, temperature 900/500°C 304.1745 MPa, temperature 920/500 °C is 269.818 MPa, for modulus raw material value is 347.53 GPa, temperature 900 /500°C is 353.1525 MPa, temperature 920/500 °C is 366.5695 MPa, for the elongation value the raw material value is 7.871%, temperature 900/500 °C is 11.392%, temperature 920/500 ° C is 13.7665%.